Antigen-responsive fluorescent antibody probes generated by selective N-terminal modification of IgGs. Issue 90 (25th October 2018) - Fukunaga, Keisuke; Watanabe, Takayoshi; Novitasari, Dian; Ohashi, Hiroyuki; Abe, Ryoji; Hohsaka, Takahiro
Abstract : Fluorescent antibody probes showing antigen-dependent fluorescence responses were developed by N-terminal-selective reductive alkylation of IgGs. Abstract : Novel fluorescent antibody probes, which show antigen-dependent fluorescence responses, were developed by selective N-terminal fluorescent labeling of IgG monoclonal antibodies using a reductive alkylation. Several kinds of IgG against tag peptides and small molecules were successfully utilized to detect antigens in a rapid and quantitative manner.